PEMBAHARUAN KONSEP KAFA’AH DALAM PERKAWINAN - Suud Sarim Karimullah; Arif Sugitanata (Jurnal Keislaman, 2022)
The purpose of this study is to reformulate efforts to renew the concept of kafa'ah in marriage which often occurs in differences among scholars. While library research is the type in this research that is studied qualitatively by compiling data systematically and is carried out through descriptive-analytic nature with a framework of thinking using deductive methods. Furthermore, this study states that the scholars have different opinions regarding the division of qualification criteria for kafa'ah in choosing a partner, but the majority of scholars argue that there is only one important and non-negotiable factor in the application of the concept of kafa'ah, namely the religious factor. Then, the renewal of the kafa'ah concept can be simplified in the division of kafa'ah qualifications into only two qualifications, namely; First, the religious factor as an important and core factor in determining the selection of a prospective partner and second, determining qualifications is returned to the two prospective brides who want to get married. This simplification aims to increase the progressiveness between the two prospective married couples and also to foster a sense of responsibility for what has been chosen in determining their partner, so that it is hoped that the desired goal of marriage will be realized, namely building a sakinah (peaceful), mawaddah (full love), wa rahmah (love).